2019
DOI: 10.12669/pjms.35.6.1031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bowel preparation on caecal intubation time during colonoscopy

Abstract: Objective: To determine the caecal intubation time depending on bowel preparation as per Boston Bowel Preparation Scale. Methods: This cross-sectional study was conducted at Dr. Ruth K. M. Pfau, Civil Hospital Karachi between August 2018 to February 2019. A total of 201 patients were included in the study. Time was recorded from insertion of colonoscope to the time required to reach the cecum. Bowel preparation was graded during withdrawal of colonoscope by using Boston Bowel Preparation Scale. Pearson C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In our study females were more; this is concordant with a study conducted by Joukar et al 16 and Alvi 17 while other studies documented more males having lower GI pathologies undergoing colonoscopy 9,18,19 . Cecal intubation rate was 58.6% in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In our study females were more; this is concordant with a study conducted by Joukar et al 16 and Alvi 17 while other studies documented more males having lower GI pathologies undergoing colonoscopy 9,18,19 . Cecal intubation rate was 58.6% in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between bowel preparation, one of the quality indicators in colonoscopy, and the CIT is not clear [4,19,20]. In our study, we found that better bowel preparation reduces CIT.…”
Section: Discussionmentioning
confidence: 51%
“…However, inadequate bowel preparation is a common problem in gastroenterological practice worldwide. Inadequate bowel cleansing adversely affects various aspects of the colonoscopy procedure, such as prolonging CIT and reducing ADRs (Alvi et al, 2019; Zhang et al, 2021). Poor preparation quality may also increase the risk of procedural-related complications (e.g., perforation, bleeding), as well as increase healthcare costs and patient discomfort due to the need for reexamination (Hotta, 2022; Murphy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%